VALIDITAS INSTRUMENT SPIN PASS DALAM PERMAINAN RUGBY - Rizqi, Nauval; Alif, Muhammad Nur; Fauzi, Rizal Ahmad (Fakultas Ilmu Keolahragaan Unimed, 2024)
Rugby is a sport played by two teams, each team consisting of five, seven, ten to fifteen players depending on the number competed. The purpose of this study was to determine the validity of the spin pass instrument for rugby games. In this study using quantitative research with descriptive methods. The sampling technique was carried out by purposive sampling. Purposive sampling represents a group of different non-probability sampling techniques. Based on the results of the validity test of the spin pass test in the rugby game, the average test between the opportunities of each participant from each distance is carried out. Then look for the total Pearson correlation from the average results of each opportunity taken by the participants. Then from the results of Pearson's correlation between distances, the researcher took the highest value from each overall distance. The highest value was obtained at a distance of 9 meters of 0.986, which will be used to test the validity of the instrument using Pearson correlation of hemisphere 1 and hemisphere 2 and even odd. In the Pearson correlation test, two values were obtained, namely 0.811 in the Pearson correlation test of hemisphere 1 and hemisphere 2 and 0.824 in the odd and even Pearson correlation test. So it can be concluded that in the odd-even pearson correlation test on the validity of the spin pass instrument, a value of 0.824 was produced, and this value can be said to be valid.